Crowdfunding, Digitalisasi dan E-Commerce dalam Upaya Pemberdayaan Ekonomi Berbasis Nilai Kearifan Lokal Bali - I Made Endra Lesmana Putra; I Putu Putra Astawa; Ni Wayan Wina Premayani (SENTRI: Jurnal Riset Ilmiah, 2026)
Digital transformation has become a major driver in the empowerment of the global economy, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. However, amid the rapid development of digital technology in Indonesia, the Hindu community still faces challenges in accessing digital markets and funding that is in line with their spiritual and social principles. This research aims to develop an e-commerce and crowdfunding based economy digitalization model that is integrated with Hindu values, especially Seva (social services), Punia (generosity), and artha_dharma (proper prosperity) to support the independence and economic welfare of Hindus in Indonesia. The results of the study show that digital platforms, if designed contextually, can be a strategic means in increasing market access, expanding funding, and strengthening the competitiveness of Hindu MSMEs. The integration of Seva and Punia principles not only strengthens the social legitimacy of digital economy practices, but also creates an ethical, inclusive, and sustainable business ecosystem. This research contributes to the development of a community economic model based on religious values in the digital era. The research data in this study was carried out by distributing research questionnaires to 165 MSMEs in Bali Province with predetermined sample criteria. This research was conducted using the survey method. All Exogenous variables consisting of Economic Digitalization, E-Commerce Use, Crowdfunding have been proven to have a positive and significant direct influence on the Endogenous Variables (Economic Empowerment). This shows that the influence of digitalization in increasing economic empowerment has been greatly felt by MSMEs, on the other hand, the application of E-Commerce in business development models, including marketing, also has a good impact on the empowerment of the MSME Economy, in addition to the Crowdfunding factor which does have a good impact on MSME capital access. The understanding of Hindu values directly also has a very good influence, the better the understanding of MSMEs about the concept of Hindu values, the more economic empowerment will increase. The Moderation hypothesis (interaction) for the three paths (Economic Digitalization, Use of E-Commerce and Crowdfunding) has not been able to moderate interaction to MSME Economic Empowerment. This is because MSME actors of Hindu values function as a strong predisposing factor or internal motivation for the ummah to be active in economic empowerment, not as a condition that strengthens the impact of programs or external factors (Economic Digitalization, Use of E-Commerce and Crowdfunding). These values are already the main driver, so their influence does not need to be mediated/moderated.